Profiles of TIC appropriation and academic performance in university students. A case study using learning analytics - Bossolasco, María Luisa; Casanova, Beatriz Adriana; Enrico, Eugenia Elizabeth; Dos Santos, Daniel Andrés; Enrico, Roxana Judith (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2018)
In this paper Learning Analytics on the students and their contexts will be used like support to the teaching and to the improvement of the processes of education-learning from an approach not "maximalista". The effective practices of the subjects will be taken into account with the aim of identify the profiles of appropriation of information and communication technology (TIC) by the students, from their digital records in the virtual classroom, in combination with quantitative data of the academic performance and users opinions. The study is applied to students of Cell Biology and Microorganisms assignment that is taught in the first semester of the first year of Bachelor and Faculty Careers in Biological Sciences in the Faculty of Natural Sciences and IML, National University of Tucumán in the academic year 2018.